2021
DOI: 10.3389/fimmu.2021.694152
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione Metabolism Is a Regulator of the Acute Inflammatory Response of Monocytes to (1→3)-β-D-Glucan

Abstract: (1→3)-β-D-Glucan (BDG) represents a potent pathogen-associated molecular pattern (PAMP) in triggering the host response to fungal and some bacterial infections. Monocytes play a key role in recognizing BDG and governing the acute host response to infections. However, the mechanisms regulating monocyte’s acute response to BDG are poorly understood. We sought to investigate the response of monocytes to BDG at the epigenetic, transcriptomic, and molecular levels. Response of human monocytes to 1, 4, and 24 hours … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
(78 reference statements)
0
5
0
Order By: Relevance
“…This activation can be inhibited with the Syk inhibitor piceatannol. It has also been shown that the exposure of myeloid cells to β-glucan modulates several cellular metabolic and epigenetic pathways that can induce cytokine production ( 72 ). Our data also suggest that elevation of specific microbiome-associated and inflammation-associated metabolic pathways may contribute to PASC, in particular, pathways with neurotoxic properties due to activation of NMDA receptors ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This activation can be inhibited with the Syk inhibitor piceatannol. It has also been shown that the exposure of myeloid cells to β-glucan modulates several cellular metabolic and epigenetic pathways that can induce cytokine production ( 72 ). Our data also suggest that elevation of specific microbiome-associated and inflammation-associated metabolic pathways may contribute to PASC, in particular, pathways with neurotoxic properties due to activation of NMDA receptors ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…This activates the NF-κB pathway and induces the secretion of proinflammatory cytokines (69)(70)(71). In addition, the exposure of myeloid cells to β-glucan can modulate several cellular metabolic (including glutathione metabolism) and epigenetic pathways that induce cytokine production (72). We, therefore, tested whether β-glucan levels correlated with markers of inflammation, as well as number of symptoms, and overall health/QoL score (Fig.…”
Section: Plasma β-Glucan Levels Associate With Markers Of Inflammatio...mentioning
confidence: 99%
“…Two pathways, starch and sucrose metabolism and androgen and estrogen biosynthesis, have been identified as important pathways in type 2 diabetes. 46 There were also several unique pathways related to oxidative stress, including glutathione metabolism, 52 vitamin A metabolism, 53 and vitamin B5 metabolism. 54 There were 12 unique pathways associated with PBB-153 in the F1 generation ( Figure 2 ; Figure S3).…”
Section: Discussionmentioning
confidence: 99%
“…193 Also, pathogen-associated molecular patterns found in microorganisms (bacteria, fungi, viruses, and protozoa) that are engaged in the detection of pathogens may change the host immune cell's epigenetic environment. It has been shown by Ramendra et al 194 that the strong pathogen-associated molecular patterns of 1,3-D-glucan from fungus were able to modify the epigenetic landscape and chromatin accessibility of monocytes. 195 On the other hand, the HBV-encoded oncogene X protein of the hepatitis B virus can alter host miRNA patterns, which then modifies the viral burden and strengthens persistence.…”
Section: The Connection Between Infection and Epigeneticsmentioning
confidence: 99%